Peran Guru Pendidikan Agama Kristen Dalam Pembentukan Karakter Siswa Menurut H.A.R. Tilaar - Anderson Ndolu; Malau, Maya; Manik, Novida Dwici Yuanri; Iswahyudi, Iswahyudi (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2022)
Christian religious education has a goal, namely, to enable people to live as Christians, namely, to live according to the Christian faith. The role of Christian religious educators is to lead people out of darkness into the Kingdom of God in Jesus. In the scriptures we find a vision of God's own plan for all mankind and creation, greetings to which Jesus the great teacher teaches His good news. It is hoped that Christian religious education teachers can carry out their duties with a sense of responsibility in accordance with educational goals and create a generation that has noble character, is responsible and has the character of Christ. The role of this Christian religious education teacher also raises a big theme in character education written by the nation's educator H.A.R. Tilaar who provides character education to strengthen the character of local culture. The purpose of this study was to determine the extent of the role of Christian religious education teachers in shaping the character of students according to H.A.R. Tilaar. Christian teachers form good characters to live in God. Living in God is not just an outward appearance, but living in God through living characters, works and thoughts that lead to God's words. The implication of a character who loves God is directly related to the character-building role of Christian education. Pendidikan agama Kristen memiliki tujuan yaitu untuk memampukan orang-orang hidup sebagai umat Kristen, yakni hidup sesuai iman Kristen. Peran pendidik agama Kristen adalah untuk menuntun orang-orang keluar dari kegelapan menuju Kerajaan Allah di dalam Yesus. Dalam kitab suci kita mendapatkan visi rencana Allah sendiri bagi seluruh manusia dan ciptaan, salam kesinambungannya Yesus sang guru agung mengajarkan kabar baik-Nya. Diharapkan guru pendidikan agama Kristen mampu melaksanakan tugasnya dengan rasa tanggung jawab sesuai dengan tujuan pendidikan dan menciptakan generasi yang berakhlak mulia, bertanggungjawab dan memiliki karakter Kristus. Peran guru pendidikan agama Kristen ini juga mengangkat tema besar dalam pendidikan karakter yang dituliskan oleh pendidik bangsa H.A.R. Tilaar yang memberikan pendidikan karakter menguatkan karakter budaya lokal. Tujuan penelitian ini adalah untuk mengetahui sejauh mana peran guru pendidikan agama Kristen dalam pembentukan karakter peserta didik menurut H.A.R. Tilaar. Guru Kristen membentuk karakter yang baik untuk hidup dalam Tuhan. Hidup dalam Tuhan bukan hanya sekadar penampakan luar, tetapi hidup dalam Tuhan melalui karakter hidup, karya serta pemikiran yang mengarah pada firman Tuhan. Implikasi dari karakter yang mengasihi Tuhan secara langsung terkait pada peran membangun karakter dari pendidikan Kristen.